Sex-Related Differences in Platelet Aggregation: A Literature Review Supplemented with Local Data from a Group of Generally Healthy Individuals - Carazo, Alejandro; Hrubša, Marcel; Konečný, Lukáš; Skořepa, Pavel; Paclíková, Markéta; Musil, František; Karlíčková, Jana; Javorská, Lenka; Matoušová, Kateřina; Krčmová, Lenka Kujovská; Parvin, Mst Shamima; Šmahelová, Alena; Blaha, Vladimír; Mladěnka, Přemysl (Seminars in Thrombosis and Hemostasis, 2022)
The process of platelet aggregation is often influenced by several factors including sex and age. A literature review confirmed the existence of sex-related differences in platelet aggregation. Although 68 out of 78 papers found such differences, there are still some controversies regarding these differences, which can be due to multiple factors (age, trigger, concomitant disease, sample handling, etc.). These outcomes are discussed in line with novel results obtained from a local study, in which blood samples from a total of 53 overall healthy women and men with ages ranging from 20 to 66 years were collected. Aggregation was induced with seven different triggers (ristocetin, thrombin receptor activating peptide 6 [TRAP-6], arachidonic acid [AA], platelet-activating factor 16 [PAF-16], ADP, collagen, or thromboxane A2 analog U-46619) ex vivo. In addition, three FDA-approved antiplatelet drugs (vorapaxar, ticagrelor, or acetylsalicylic acid [ASA]) were also tested. In general, women had higher aggregation responses to some agonists (ADP, TRAP), as well as lower benefit from inhibitors (ASA, vorapaxar). The aggregatory responses to AA and TRAP decreased with age in both sexes, while responses to ADP, U-46619, and PAF were affected by age only in women. In conclusion, more studies are needed to decipher the biological importance of sex-related differences in platelet aggregation in part to enable personalized antiplatelet treatment.
Keywords: platelet aggregation; blood coagulation; antiplatelet drug; correlation of data; sex differences